2020
DOI: 10.1029/2020jb020988
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Episodes of Fluid Infiltration Along a Single Metasomatic Channel in Metacarbonates (Mogok Metamorphic Belt, Myanmar) and Implications for CO2 Release in Orogenic Belts

Abstract: Fluid infiltration into metacarbonates is a key mechanism to induce orogenic decarbonation, which influences the global carbon cycle and long‐term climate evolution. Little is known regarding the fluid pathways during episodic infiltration events and how flow patterns control time‐integrated CO2 outflux. We investigate the “vein‐like” polycrystalline mineral reaction zones (PMRZs) in dolomite marbles (Mogok metamorphic belt, Myanmar), which are formed by metasomatism via the infiltration of Si–Al–K–Ti–Zr‐beari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 88 publications
(171 reference statements)
0
12
0
Order By: Relevance
“…Although there are effects from fluid derived from underlying dehydrating lithologies, fluid infiltration in subducted marbles mostly occurs at low pressures of <2.0 GPa 9 , 33 because two-thirds of the water in the fully hydrated oceanic crust would be lost at forearc depths 12 . Furthermore, marbles are notably impermeable to fluid flow 34 , 35 compared to silicate rocks, thus fluid infiltration usually occurs along a single channel in the subducted marbles 9 , 36 . The water content of the limestone used in our experiments is 0.9 wt.% and was probably higher during experiments due to hydrogen diffusion, thus could represent the water content of natural marbles at subarc depths.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are effects from fluid derived from underlying dehydrating lithologies, fluid infiltration in subducted marbles mostly occurs at low pressures of <2.0 GPa 9 , 33 because two-thirds of the water in the fully hydrated oceanic crust would be lost at forearc depths 12 . Furthermore, marbles are notably impermeable to fluid flow 34 , 35 compared to silicate rocks, thus fluid infiltration usually occurs along a single channel in the subducted marbles 9 , 36 . The water content of the limestone used in our experiments is 0.9 wt.% and was probably higher during experiments due to hydrogen diffusion, thus could represent the water content of natural marbles at subarc depths.…”
Section: Discussionmentioning
confidence: 99%
“…During this period, episodic fluid infiltrations (i.e., $36-35 Ma, $24-23, Ma, and $17 Ma) into metacarbonates (marbles) of this region may have also contributed to regional metasomatism and subsequent ruby mineralization (Guo et al, 2021). A recent study reported titanite SIMS U-Pb ages of $25 Ma for ruby-bearing marbles, suggesting that the ruby mineralization was probably related to the high-temperature metamorphism during the India-Asia collision (Zhang et al, 2021).…”
Section: Geological Setting and Sample Descriptionmentioning
confidence: 97%
“…As discussed above, our data for the Mogok ultramafic rocks show that they are probably Alaskan-type cumulates generated from subduction-related arc magmas. Based on regional geological evolu- belonging to cumulates, were generated in the Jurassic-Lower Cretaceous, they were unrelated with the Cenozoic metamorphism and magmatism in this region, which provided heat for gemstone mineralization (Guo et al, 2021;Searle et al, 2020). Second, if the Mogok ultramafic rocks formed during the Upper Cretaceous-Cenozoic, their emplacement could provide additional heat for the regional metamorphism and magmatism.…”
Section: Tectonic Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metasomatic skarns occur in contact zones between the marbles and intrusions as a function of the infiltration of fluids/melts. Metasomatism may form various mineralogical reaction zones in which rare gems are produced [5,8,30,35].…”
Section: Geological Setting and Sample Descriptionmentioning
confidence: 99%